Regionálny manažmentteória, prax a rozvoj - Hittmár, Štefan (Univerzita Pardubice, 2002)
The paper deals with model of management in region's conditions. In first part, it describes regional management and regional marketing. In this part there are described aspects of regional management from the science and art point of view. In second part describes six elements of model of regional management. It explains the basic subject of this elements. On the and there is processed the definition of regional management.
Keywords: řízení; Region; systémy; Strategie; Lidské zdroje; Management